Pictorial Ekphrasis in the Work of V.F. Odoevsky (Based on the Story "The Painter") - Ю.Г. Цой (Scientific Trends, 2024)
The article reveals the specificity of pictorial ekphrasis in the work of V.F. Odoevsky. On the example of the story "The Painter" the theme of art and its constituent images and motifs are revealed.
Keywords: Ekphrasis, functions of ekphrasis in a literary text, art, painting.